Improving Supply Chain Resilience Through Fintech Technology in the Digital Age - Sintesa, Nika; Astutik, Wahyuni Sri (West Science Journal Economic and Entrepreneurship, 2025)
This study investigates the impact of financial technology (fintech) adoption on supply chain resilience in the digital age. Using a quantitative approach, data were collected from 76 respondents representing various business sectors that have integrated fintech solutions into their supply chain operations. The research instrument employed a five-point Likert scale, and data analysis was conducted using SPSS version 25. Supply chain resilience was measured through four dimensions: agility, visibility, flexibility, and risk mitigation. Validity and reliability tests confirmed the robustness of the measurement instruments. Descriptive analysis indicated high average scores for all variables, while regression analysis revealed that fintech adoption had a positive and significant effect on all four resilience dimensions, with the strongest effect observed on visibility. These findings highlight fintech’s strategic role in enhancing transparency, operational agility, adaptability, and proactive risk management. The study provides actionable insights for managers and policymakers to integrate fintech solutions as a core component of supply chain strategy, particularly in preparing for and responding to disruptions in a rapidly evolving digital environment.